Evaluation of Land Suitability in Other Use Areas for Local Avocado Production In Muntok Sub-District, West Bangka Regency - Riski Meliya Ningsih; Adhitya Vishnu Pradana; Abi Barokah; M. Fiu Muthi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2025)
The limited availability of fertile land in Bangka Island, driven by the high rate of land conversion and the persistent impacts of mining activities, has become increasingly critical. This condition has intensified the urgency to utilize Other Use Areas (APL) for the development of high-economic-value commodities. This study aims to evaluate the potential and suitability level of APL in Muntok Sub-district, West Bangka Regency, as a cultivation site for local avocado (Persea americana). The method used was a descriptive survey with a spatial approach employing Geographic Information Systems and Land Suitability Evaluation (FAO Matching Method). Analysis was conducted on a total of 3,029 hectares of APL by measuring bio-physical soil parameters (pH, organic carbon, drainage) and climate data, which were then matched with optimal growth criteria for avocado. The land suitability evaluation results showed that the study area has no Very Suitable (S1) class. The land was dominated by Moderately Suitable (S2) class covering 66.55% and Marginally Suitable (S3) class covering 20.30%, while 13.15% was classified as Not Suitable (N). Although agroclimatic factors were within optimal limits (S1), edaphic factors were the most critical limiting factors. The main constraint was very low organic carbon content (average 1.18–1.71 g.kg⁻¹) and acidic soil reaction (pH 4.5–5.4), which collectively inhibit nutrient uptake by plants. It is concluded that the potential of APL in Muntok can be significantly improved from S2/S3 to an actual suitability class of S1. The implication of this study is a strategic recommendation for policymakers and farmers to prioritize specific interventions, namely liming to remediate acidity and intensive application of organic materials to enhance soil fertility, thereby supporting sustainable horticulture diversification programs, especially with avocado, in West Bangka. Keywords: acidity remediation, descriptive survey, edaphic factors, land conversion, land limitation